2006
DOI: 10.1111/j.1365-2141.2006.06126.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study on the behaviour of the metalloprotease ADAMTS13 and of von Willebrand factor after bone marrow transplantation

Abstract: Summary Thrombotic microangiopathies (TMAs) are rare but serious complications of bone marrow transplantation (BMT). Clinical manifestations are similar to those of thrombotic thrombocytopenic purpura (TTP), but prognosis is generally poorer despite plasma exchange. The enzymatic activity of the plasma metalloprotease ADAMTS13, which cleaves ultralarge thrombogenic multimers of von Willebrand factor (VWF) derived from activated endothelial cells, is very low or undetectable in patients with classic TTP, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 40 publications
3
32
2
Order By: Relevance
“…34 Why should PE be effective in management of TA-TMA, when, unlike idiopathic TTP, TA-TMA has not been associated with autoantibody production and/or severe deficiency of the plasma protease ADAMTS13? 8,[27][28][29] Although the exact mechanisms involved in pathogenesis of TA-TMA in different clinical settings post-SCT are not currently known, the development of endothelial cell injury or dysfunction seems to represent a final common pathway in the pathogenesis of MAHA post-SCT. 2,3 Several drugs used in SCT, and various cytokines associated with GVHD and other post-SCT complications, can potentially induce endothelial cell apoptosis and/or dysfunction, including calcinuria inhibitors, IL-1 and TNFa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Why should PE be effective in management of TA-TMA, when, unlike idiopathic TTP, TA-TMA has not been associated with autoantibody production and/or severe deficiency of the plasma protease ADAMTS13? 8,[27][28][29] Although the exact mechanisms involved in pathogenesis of TA-TMA in different clinical settings post-SCT are not currently known, the development of endothelial cell injury or dysfunction seems to represent a final common pathway in the pathogenesis of MAHA post-SCT. 2,3 Several drugs used in SCT, and various cytokines associated with GVHD and other post-SCT complications, can potentially induce endothelial cell apoptosis and/or dysfunction, including calcinuria inhibitors, IL-1 and TNFa.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,8 Unlike idiopathic TTP, TA-TMA has only rarely been associated with severe deficiency of the plasma protease ADAMTS13. 8,[27][28][29] Current therapeutic recommendations of TA-TMA revolve around treatment of and/or elimination of conditions resulting in endothelial insult. 2,3 These recommendations include immediate cessation of potential culprit medications and aggressive treatment of associated GVHD and/or infection.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, numerous reports suggest that the use of CsA in transplant patients may be associated with TTP (12)(13)(14)(15)(16), although some other reports reveal no interrelationship between CsA treatment and TTP development and found no influence of CsA treatment on ADAMTS13 levels (17). Nevertheless, it has been demonstrated that reduced activity and/or deficiency of ADAMTS13 can clinically manifest as TTP (18).…”
Section: The Von Willebrand Factor (Vwf)mentioning
confidence: 99%
“…Furthermore, Au et al (2007) found no change in ADAMTS13 and anti-ADAMTS13 after treatment with rituximab. The genesis of TM after transplant may be more related to endothelial damage rather than an antibodymediated lowering of ADAMTS13 levels (Peyvandi et al, 2006).We wonder whether rituximab was really responsible for the regression of TM in this small cohort of patients, rather than possible alternative contributory factors, e.g. the replacement of ciclosporin with tacrolimus and the use of steroids, which can probably control graft-versus-host disease (a known risk factor for TM), in three out of four responding patients.…”
mentioning
confidence: 99%
“…Furthermore, Au et al (2007) found no change in ADAMTS13 and anti-ADAMTS13 after treatment with rituximab. The genesis of TM after transplant may be more related to endothelial damage rather than an antibodymediated lowering of ADAMTS13 levels (Peyvandi et al, 2006).…”
mentioning
confidence: 99%